Моделювання процесу видалення золи із газу в скрубері Вентурі з урахуванням турбулентних пульсацій швидкості частинок - Shraiber O.A.; Antonets I.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2014)
Improvement of the efficiency of the cleaning of flue gases of coal-fired boilers from ash particles is an important environmental problem. In the power engineering of Ukraine, apparatus for the wet cleaning of flue gases are widely spread, especially Venturi scrubbers. Their characteristics often do not meet the present-day requirements, although the possibilities of improvement of their work are far from being exhausted. The most reasonable way of solution of this problem is connected with mathematical modeling. Earlier, the authors have built such a model. In the present work, we describe the generalization of this model with regard for the effect of turbulence of gas flow.The work consists of two parts. First, approximating the distribution of fluctuation velocities of gas moles and particles by Maxwellian functions, we determine the average velocity of fluctuation slip between two fractions. Second, we find relations for calculating the effective slip velocity of particles with regard for their both averaged and fluctuation motion. We determine the domain where the proposed method of calculating the effective slip velocity enables one to obtain more exact data as compared with the known, approximate approach.